Double tongue in a buffalo calf - Rafee, Malik Abu; Bhat, Abas Rashid; -, Amarpal (Buffalo Bulletin, 2018)
A new born male buffalo calf was presented with two double tongue, hanging one on either side of outgrowth from base of the mouth. The out growth had few small teeth like structures over it. The head of the calf was relatively longer than body. There was no other associated congenital anomaly. The case was managed by surgical excision of one tongue and outgrowth.